Performance evaluation and improvement of IEEE 802.11 MAC protocol in wireless ad-hoc networks - Li, Zhifei (2008)
In this thesis, the main objective is to evaluate and improve the performance of IEEE 802.11 MAC protocol in wireless ad-hoc networks.